Pengembangan E-Modul Matematika Berbasis Potensi Wisata Kota Pasuruan pada Materi Bangun Ruang Sisi Datar - Vika Zida Akmaliah; Andika Setyo Budi Lestari; Miftahul Khoiri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The purpose of this study is to develop a mathematics e-module based on the tourism potential of Pasuruan City material of flat-sided solid shapes. This research is motivated by the use of teaching materials by teachers is still manual, not in digital form that integrates local tourism potential. The type of research is R&D (Research and Development) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of the study show that the mathematics e-module based on the tourism potential of Pasuruan City material of flat-sided solid shapes has gone through a model development process. The validation results show that the percentage of experts with an average of 93.6% is in the very valid category. The application of the mathematics e-module received a positive response with a percentage of 88.5% on a small scale and on a large scale showing 89.2% in the very practical category. The posttest showed a percentage on a small scale of 83%, while on a large scale it reached 80% which is categorized as effective. Conclusion, the development of a mathematics e-module based on the tourism potential of Pasuruan City material of flat-sided solid shapes is declared valid, practical and effective.